Import substitution in high-tech industries under external sanctions - N. M. Abdikeev (Управленческие науки)
In the context of restrictions on the import of technologies and equipment to the Russian Federation caused by external sanctions and the withdrawal of Western European, American and Japanese companies from our country, initially, high-tech branches of domestic industry found themselves in a difficult situation. There were problems related to the substitution of products that fell under the ban on import, and the development of localization of the main production segments. The purpose of the study is to review import substitution plans in the machine tool, aviation, electronic and machine-building industries in order to assess the effectiveness of their implementation; to identify the causes and factors of inhibition of the import substitution policy, as well as ways to improve its effectiveness. The author offers directions of improvement of the State support of high-tech branches of manufacturing industry to solve the problems facing it.